1971
DOI: 10.1085/jgp.57.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Active Uptake of Ca++ and Ca++-Activated Mg++ ATPase in Red Cell Membrane Fragments

Abstract: Isolated human red blood cell membrane fragments (RBCMF) were found to take up Ca++ in the presence of ATP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(27 citation statements)
references
References 6 publications
5
22
0
Order By: Relevance
“…If this is the case, then the different results obtained in their and the present study may be reconciled by assuming that Ca ++ is required for the step from E1-P to Ez-P. Since the Ca ++ transport ATPase is very sensitive to temperature and no dephosphorylation occurs at 0°C (Cha et al, 1971), the presence of Ca ++ would increase phosphorylation by forming E2-P without dephosphorylation of this intermediate at 0°C in the study of Knauf et al (1974 b). As discussed by the authors in their study, another cause of increased phosphorylation by Ca ++ was the inhibition of dephosphorylation of Na+-K+-ATPase by Ca ++.…”
supporting
confidence: 46%
See 4 more Smart Citations
“…If this is the case, then the different results obtained in their and the present study may be reconciled by assuming that Ca ++ is required for the step from E1-P to Ez-P. Since the Ca ++ transport ATPase is very sensitive to temperature and no dephosphorylation occurs at 0°C (Cha et al, 1971), the presence of Ca ++ would increase phosphorylation by forming E2-P without dephosphorylation of this intermediate at 0°C in the study of Knauf et al (1974 b). As discussed by the authors in their study, another cause of increased phosphorylation by Ca ++ was the inhibition of dephosphorylation of Na+-K+-ATPase by Ca ++.…”
supporting
confidence: 46%
“…Previously, it was found that when red blood cells are fragmented, red blood cell membrane fragments (RBCMF) were found to take up Ca ++ and this Ca ++ uptake is accompanied by ATP hydrolysis by Mg++-activated ATPase (Lee and Shin, 1969;Cha et al 1971). It has been suggested that this Ca ++ uptake is due to the presence of inside out vesicles in the present system although not all of the vesicles are inside out (Steck et al, 1970;Weiner and Lee, 1972).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations